AN ANALYSIS OF THE INTEGRATION OF NAQLI AND AQLI ELEMENTS IN THE ENGLISH FOR ACADEMIC PURPOSES COURSE: A CASE STUDY IN USIM - Yuslina Mohamed; Maziahtusima Ishak; Ezihaslinda Ngah; Hazlina Abdullah; Normazla Ahmad Mahir (Journal of Islamic, Social, Economics and Development, 2018)
For a long time, there has been an element of dualism in the education system, and research has shown that there has been a great concern among many Muslim countries that university graduates live a life not in line with the Islamic values advocated in the Quran and the Sunnah. This stems from the value crises that lie within the values transpired to the students, whereby there are gaps between the worldly knowledge (Aqli) and the Islamic knowledge (Naqli) which results in imbalanced graduates—secularised minds versus the conservative ones. Both groups are incapable in performing the ‘right’ role of a khalifah for the betterment of the ummah, as one is more equipped with the worldly knowledge, and viceversa. This study looks at the curriculum of English for Academic Purposes (EAP) course conducted at USIM—whether or not the elements of Naqli and Aqli are being integrated in the curriculum. Findings reveal that the integration of Naqli and Aqli elements in the EAP course is still at the initial stage as could be seen through the related documents of the course, and also based on the instructors’ views. The elements are superficially and loosely integrated, merely through the mention of the phrase ‘Naqli and Aqli’ but without clear guidelines of how it could be more systematically implemented, especially for language courses. The study is hoped to fill the gap, and contribute in the development of integrating Naqli and Aqli elements for a language course in general, and for EAP specifically.